A Discipline Divided Schools and Sects in Political Science - Almond, Gabriel A. (Sage Publications, 1990)
A Discipline Divided is a collection of coherent and timely articles that discuss the emergence and divergence of the two dominant camps of political science: ideology and methodology. Almond examines the `hard′ versus `soft′ science argument, the history of model fitting in communism studies, the strengths and weaknesses of the rational choice movement and the historical forces and processes that have shaped political culture.